Cervical intraepithelial neoplasia II-III with endocervical cone margin involvement after cervical loop conization: Is there any predictor for residual disease? - Chumnan Kietpeerakool (2018)
Aim: To determine the clinicopathological predictors for residual disease in women who have had cervical intraepithelial neoplasia (CIN) II-III with endocervical cone margin involvement after loop electrosurgical excision procedure (LEEP). Methods: All of the women who had CIN II-III on LEEP specimens with endocervical margin involvement, and underwent subsequent surgical treatment including repeat LEEP or hysterectomy at Chiang Mai University Hospital between May 2003 and June 2006 were reviewed. Results: During the study period, 85 women who matched the study inclusion were identified. The mean age was 48.6 years. Fifty-two women (61.2%) were postmenopausal. The most common Pap smear before LEEP was high-grade squamous intraepithelial lesion (HSIL) (65.9%), followed by squamous cell carcinoma (21.2%). Twenty-five women (29.4%) had concurrent ectocervical and endocervical cone margin involvement. Residual disease was noted in 44 women (51.8%, 95%CI = 40.7-62.7) of whom six had unrecognized invasive squamous cell carcinoma, while the remaining 38 had CIN II-III. Only extensive endocervical cone margin involvement (3-4 quadrants) was noted as the significantly independent predictor for residual disease (aOR = 14.2, 95% CI = 3.6-55.8; P < 0.001). Conclusion: Extensive endocervical cone margin involvement after LEEP for CIN II-III is a strong predictor for residual disease. Therefore, the number of involved quadrants should be evaluated to plan further management. © 2007 The Authors.